Corporate Governance Drives Energy Sector Firm Value Indonesia: Tata Kelola Perusahaan Mendorong Nilai Perusahaan Sektor Energi Indonesia - Kristianto, Moh. Frendy; Darmayanti, Novi; Wafa, Moh. Ali (Academia Open, 2026)
General Background: Firm value is a critical indicator for investors in evaluating corporate performance and future prospects, particularly in capital markets. Specific Background: In recent years, green finance, corporate sustainability, and good corporate governance have emerged as key factors associated with firm value, especially within energy sector companies listed on the Indonesia Stock Exchange during 2020–2024. Knowledge Gap: Prior studies show inconsistent findings regarding the roles of sustainability and governance variables, and limited research integrates these three variables simultaneously in the energy sector context. Aims: This study aims to analyze the relationship between green finance, corporate sustainability, and good corporate governance on firm value using panel data regression based on secondary data from 12 companies (60 observations). Results: The findings indicate that green finance and corporate sustainability do not show significant relationships with firm value, while good corporate governance demonstrates a positive and significant relationship by improving transparency, accountability, and reducing agency risk. Novelty: This study integrates three key variables within a single empirical model focused on the energy sector, providing updated evidence in the Indonesian context. Implications: The results suggest that companies should prioritize governance practices while strategically integrating sustainability, investors may emphasize governance indicators in decision-making, and regulators need to improve sustainability reporting quality to increase market relevance. Highlights• Governance mechanisms associated with higher market valuation indicators• Sustainability disclosure not linked to immediate market response• Environmental financing adoption remains limited in short-term valuation KeywordsGreen Finance; Corporate Sustainability; Good Corporate Governance; Firm Value; Energy Sector